Analysis of methods to ensure the quality of service in high-speed computer networks - Кудзиновская, И. П. (Problems of Informatization and Control, 2008)
The methods of QoS in networks . The influence of the properties of self-similarity traffic performance QoS. The necessity of the development of algorithms for shaping and congestion avoidance based on self-similar traffic